# Simplify this equation: `-5(1+2i)(4+sqrt(-1))`

### 2 Answers | Add Yours

Take note that `sqrt(-1) = i.`

Hence, we will have:

`-5(1 + 2i)(4 + i) `

We use foil method here.

`-5((1*4) + (1*i) + (2i*4) + (2i*i)) = -5(4 + i + 8i + 2i^2)`

Combine like terms.

`-5(4 + 9i + 2i^2)`

Take note that i^2 = -1.

`-5(4 + 9i + 2(-1)) = -5(4 + 9i - 2) = -5(2 + 9i)`

Apply Distributive Property.

`-5(2 + 9i) = -10 - 45i`

Therefore, the **answer is -10 - 45i**.

` `

` `

`-5(1+2i)(4+i)=-5(4+i+8i+2i^2)=-5(4+9i-2)=-5(2+9i)`